Cortisol in sickle cell disease: a systematic review and meta-analysis - Kemar V. Prussien; Margaret Mary Burke; Kandace Gollomp; Rosalind J. Wright; Alexis A. Thompson (Blood Advances)
Abstract: Cortisol plays a critical role in the biological link between psychosocial stress and health outcomes; however, the methods for assessing cortisol and the biopsychosocial correlates of this stress hormone among individuals with sickle cell disease (SCD) are not well developed. This review aimed to systematically evaluate the current literature for cortisol measurement and methodology among individuals with SCD and synthesize findings of biopsychosocial correlates in this population. A systematic search of medical databases was conducted, resulting in 20 studies meeting inclusion criteria, involving 710 participants with SCD and 454 control participants without SCD. Cortisol was primarily measured using serum (k = 10) and plasma (k = 8), and few studies used salivary (k = 1) or hair (k = 1) measurements. Most studies investigated cortisol in comparison with a control group (k = 14). Qualitative findings were inconsistent, and quantitative meta-analytic data (k = 12) imply no significant difference in cortisol in SCD participants relative to healthy controls (serum Hedges g = −1.51, 95% confidence interval [CI], −3.99 to 0.97; plasma Hedges g = −0.72; 95% CI, −1.56 to 0.13). Additionally, studies examined cortisol in comparison with adrenal standards (k = 5), responses to adrenocorticotropic hormone stimulation (k = 7), and correlations with vaso-occlusive crises (k = 3) and disease severity (k = 3). Few studies explored medication (k = 2) or behavioral correlates (k = 1) of cortisol. Finally, no study investigated the influence of psychosocial stressors on cortisol levels. There is a clear need for high-quality observational research to clarify cortisol findings in SCD and identify psychosocial correlates and biomedical outcomes.